Moslem women - Zwemer, Samuel Marinus, 1867-1952. (Piscataway, NJ)
xxvii, 272 sayfa, [24] sayfa resim
Keywords: “Moslem Women is built around six main chapters; half are devoted to the place and experiences of Moslem women, and half consider the Christian mission to these women. The Zwemers acknowledge some of the great women of Islamic history, such as Rabia, the famous early mystic, and Nurah Mahal, wife of the Mughal Emperor Jahangir. They speak in glowing terms about advances in the women’s situation in post-Ottoman Turkey. Their work is dedicated to serving Muslims and to seeing them as people rather than as faceless numbers; it is an excellent model for today’s Christians who feel called to engagement with Islam“ -- Yayıncı.